Synthesis, characterisation of agricultural biomass derived activated carbon and its applications - Shweta Priya; Salmataj S A; B Anusha; Pushpanjali Bhat (Materials Research Express)
As the world moves toward greener energy generation methods and cleaner environments, activated carbon produced from ligninocellulosic resources has attracted unexpected interest due to its easy availability, and economic, renewable, and biodegradable properties, which makes it a viable alternative to exhaustible coal. This review paper provides a comprehensive overview of a systematic procedure to develop activated carbon from plant biomass, its characterization by simple techniques, and the versatile applications of activated carbon. This includes its role in environmental remediation, from emphasizing its efficacy in removing a wide array of pollutants, to sustainable methods of hydrogen capture and energy storage in supercapacitors. A brief comparison of the key aspects of optimal toxicant adsorption, like batch conditions, the best-fit model, isotherms, and maximum adsorption, are also made. To ascertain the efficiency of the supercapacitors, their strategy in designing it, and their output in terms of specific capacitance, power, and energy density are compared.